1976
DOI: 10.1093/jn/106.8.1115
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Lack of an Effect of Dietary Fluoride Level on Reproduction in Mice

Abstract: The possible essentiality of fluoride for reproduction was studied in female mice fed a low-fluoride ( less than 0.5 ppm F) basal diet for three generations. Reproduction of mice fed this basal diet was the same as when mice were fed the basal diet supplemented with 2 or 100 ppm F. A previous study [Messer et. al. (1973) J. Nutr. 103, 1319-1326], utilizing the same diet did result in an impairment of reproduction and the development of an anemic condition. The results of the present study suggest that the appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

1982
1982
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 17 publications
1
6
0
2
Order By: Relevance
“…A decrease in cauda epididymal sperm count in mice, rats, and rabbits has been reported after fluoride ingestion Chinoy and Sharma 2000;Chinoy et al 1991Chinoy et al , 2006Wan et al 2006). On the other hand, Tao and Suttie (1976) reported that fluoride does not play a disruptive role in mammalian reproduction. Moreover, Sprando et al (1997) indicated that fluoride does not adversely affect spermatogenesis at 25, 100, 175, and 250 mg fluoride/liter in the drinking water of male rats.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in cauda epididymal sperm count in mice, rats, and rabbits has been reported after fluoride ingestion Chinoy and Sharma 2000;Chinoy et al 1991Chinoy et al , 2006Wan et al 2006). On the other hand, Tao and Suttie (1976) reported that fluoride does not play a disruptive role in mammalian reproduction. Moreover, Sprando et al (1997) indicated that fluoride does not adversely affect spermatogenesis at 25, 100, 175, and 250 mg fluoride/liter in the drinking water of male rats.…”
Section: Discussionmentioning
confidence: 99%
“…[4] These reports were contradicted by Tao and Suttie, whose experiments showed that fluoride did not play any essential role in reproduction. [5] Because of these controversial reports, we intended to assess the effect of fluoride on the rabbit reproductive system.…”
Section: Introductionmentioning
confidence: 99%
“…In a study, mice fed low F diets developed anemia and impaired reproduction (Messer et al 1972(Messer et al , 1973. However, later on, it was found that anemia and impaired reproduction were due to low dietary iron and no such symptoms developed when mice were fed a diet containing low fluoride and sufficient iron (Tao and Suttie 1976). Another study reported skeletal abnormalities in female goats and poor growth in their offspring when they were fed a diet containing less than 0.3 ppm fluoride (on a dry matter basis) for 10 generations (Anke et al 1997).…”
Section: Fluoride and Animal Healthmentioning
confidence: 99%